Down-Regulation of Tim-3 in Monocytes and Macrophages in Plasmodium Infection and Its Association with Parasite Clearance - Hou, Nan; Jiang, Ning; Zou, Yang; Piao, Xianyu; Liu, Shuai; Li, Shanshan; Chen, Qijun (Frontiers in Microbiology, 2017)
T-cell immunoglobulin- and mucin-domain-containing molecule 3 (Tim-3) has complicated roles in regulating monocytes and macrophages in various diseases and it tends to be an inhibitory molecule to facilitate the immune escape of parasites in malaria. However, the mechanisms of Tim-3 mediated responses in monocytes and macrophages in malaria have not been clear. In this study, we found that Plasmodium infection down-regulated Tim-3 expression in peripheral monocytes of patients suffering from Plasmodium falciparum malaria and in splenic macrophages of Plasmodium berghei ANKA-infected mice. Tim-3 signal blockade with anti-Tim-3 antibodies enhanced phagocytosis and parasitical mediator production of murine splenic macrophages during Plasmodium infection. In conclusion, Tim-3 constricts monocytes/macrophages activity, and anti-Tim-3 treatment facilitates parasite clearance, especially in the early stage of Plasmodium infection.